Knowledge and Perception of Iraqi Pharmacists Towards Biosimilar Medicines - Ashwaq J. Mohammed; Dheyaa J. Kadhim (College of Pharmacy University of Baghdad, 2021)
Abstract Biosimilars are non-innovative copy versions of biologic medicines which are proven to be clinically equivalent to, as effective and as safe as their reference biologics. Biosimilars creates opportunities for cost savings for payers, governments, and patients compared with the reference products. Pharmacist plays an essential role in developing biosimilar medicines from manufacturing to post-marketing pharmacovigilance monitoring. The aim of the current study was to explore  the level of  knowledge, behaviors and practices of  a sample of Iraqi pharmacists towards biosimilar medicines.  The current study was a cross sectional, carried out during May 2020. A total of 264 pharmacists  )143 male, 121 female) were involved in this study.  A web-based self-administered questionnaire was used for data collection . Regarding pharmacists' knowledge of biosimilar medicines, the results showed that two questions received the highest percentages of adequate answers: biosimilar medicine requires preclinical and clinical studies (58.0%) and biosimilar medicines require more comprehensive data compared to generic drugs (56.1%). In contrast, marketing authorization of biosimilar medicines is granted on the sole investigation of pharmacokinetic bioequivalence received the lowest percentage of adequate answers (21.6%). In addition, the current study showed that more experience years and male gender associated with better knowledge.  With respect to perceptions of pharmacists  about biosimilar medicines, two statements received the highest percentage of pharmacist agreements: biosimilar medicines are tested in terms of efficacy and safety (64.4%) and biosimilar prescription allows for reducing costs (64.4%). At the same time, 40.2% of the participating pharmacists agreed with pharmacist replacing a reference biologic medicines with its biosimilar product. In conclusion, the majority of the surveyed pharmacists had insufficient knowledge towards biosimilar medicines. The study highlighted that Iraqi pharmacists needed more accurate  comprehensive information concerning biosimilar medicines.